2018
DOI: 10.2174/1573403x14666180522124621
|View full text |Cite
|
Sign up to set email alerts
|

Triple-Valve Endocarditis in a Diabetic Patient: Case Report and Literature Review

Abstract: In this paper we describe the case of a 48-year-old male who was diagnosed with triple-valve endocarditis and provide a review of the literature to delineate what is already known and improve our understanding of this rare phenomenon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Triple-valve replacement for active IE is highly infrequent: besides the six cases gathered by Kadado [2] , we only found three more [9] , [10] , [11] . None of these nine cases combined underwent surgery after septic shock.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Triple-valve replacement for active IE is highly infrequent: besides the six cases gathered by Kadado [2] , we only found three more [9] , [10] , [11] . None of these nine cases combined underwent surgery after septic shock.…”
Section: Discussionmentioning
confidence: 81%
“…Triple-valve surgery is rarely performed in infective endocarditis (IE) (<2 % of procedures in the Italian IE Registry) [1] , and triple-valve replacement in IE is even less often: a 2018 review of the literature identified only six reported cases [2] . We report a case of Rhizobium radiobacter ( R. radiobacter ) triple-valve IE presented in septic shock affecting a young patient with neglected ventricular septal defect (VSD).…”
Section: Introductionmentioning
confidence: 99%
“…Most of our understanding of TVE comes from limited clinical case reports, with a 2018 paper noting only 16 published cases. 2 Given this, much of the data regarding epidemiology and management of TVE is derived from a broader category of multivalvular endocarditis (MVE), which incorporates infections involving two or more valves. MVE is also infrequent, though rates of up to 18% have been identified among endocarditis cases.…”
Section: Discussionmentioning
confidence: 99%
“…Triple (TVE) or quadruple valve endocarditis is rare and infrequently described in the literature. Here we describe a case of TVE in an IV drug user 2 and provide a literature review of TVE identification, treatment, and prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of IE cases typically involve only one valve, with two valve involvement being less frequent and triple or quadruple valve involvement reported to be extremely rare [6]. Interestingly, mortality rates seem to be similar between single and multiple valve IE, however, multivalvular involvement has an increased rate of congestive heart failure (CHF) complications requiring surgical management [7][8].…”
Section: Introductionmentioning
confidence: 99%